Sulfate reduction rates determined in whole-core incubations with 35S-SO42- in sediments from Young Sound, NE Greenland - Ingrid Wiedmann; Maria Lund Paulsen; Johnna M Holding; Mie Hylstofte Sichlau Winding; Hans Roy; Mikael K Sejr; Katja Laufer-Meiser (PANGAEA, 2025)
This dataset contains measurements of sulfate reduction rates in sediments from Young Sound. The samples for the measurements were taken in August 2019 with a Kajak-corer.
In: Wiedmann, I et al. (2025): Impact of Different Types of Meltwater Runoff on Pelagic and Benthic Processes in Young Sound, NE Greenland [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.986456